KUALITAS PELAYANAN PENGURUSAN PASPOR PADA KANTOR IMIGRASI KELAS I SEMARANG - Wildan Jaya Aksara; Muhammad Mustam; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The research was motivated by the problems that occurred in the management of passport at the immigration office grade 1 Semarang, among them are the practices of corruption, discrimination service. Purpose this study to describe the quality of service management of passport at the immigration office grade 1 Semarang. In answer to the problem and purpose of this study, the author uses the theory of public services, and quality of service by using descriptive qualitative research methods. In collecting the data, the authors use the way through the interview, informants selected observation. The include immigration officials and the public. The results showed the quality of service at the immigration office grade 1 Semarang. Suggested order to increase the number of tablespoons so the service provided in order to optimize.